Factor V Leiden Is Associated with Repeated and Recurrent Unexplained Fetal Losses - Grandone, Elvira; Margaglione, Maurizio; Colaizzo, Donatella; d'Addedda, Marina; Cappucci, Giuseppe; Vecchione, Gennaro; Sciannamé, Natale; Pavone, G; Di Minno, G (Thrombosis and Haemostasis, 1997)
Activated protein C resistance (APCR) is responsible for most cases of familial thrombosis. The factor V missense mutation Arg506>Gln (FV Leiden) has been recognized as the commonest cause of this condition. Recently, it has been suggested that APCR is associated with second trimester fetal loss. We investigated the distribution of FV Leiden in a sample (n = 43) of Caucasian women with a history of two or more unexplained fetal losses. A group (n = 118) of parous women with uneventful pregnancies from the same ethnical background served as control. We found the mutation in 7 cases (16.28%) and 5 controls (4.24%; p = 0.011). A statistically significant difference between women with only early fetal loss vs those with late events (p = 0.04) was observed. Our data demonstrate a strong association between FV Leiden and fetal loss. Furthermore, they indicate that late events are more common in these patients.